2006
DOI: 10.1136/bjo.2006.110221
|View full text |Cite
|
Sign up to set email alerts
|

The effect of changing intraocular pressure on the corneal and scleral curvatures in the fresh porcine eye

Abstract: Aim: To measure corneal and scleral radii of curvature in response to intraocular pressure (IOP). Methods: Using digital photographic profile images of 16 fresh porcine eyes, the curvatures of the cornea and sclera were determined in response to five consecutive incremental 100 ml saline intravitreal injections. IOP was measured and ocular rigidity calculated. Elastic moduli of the cornea and sclera were estimated. Results: Intraocular pressure and the radius of curvature of the sclera increased linearly with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 10 publications
7
61
1
2
Order By: Relevance
“…20 This suggested that the sclera is stiffer than the cornea, providing key structural support to the eye. The scleral tangent moduli of porcine eyes measured in this study are comparable to the results reported by Pierscoionek et al 26 using the inflation test (0.2-0.5 MPa, the testing IOP ranged from 15-50 mm Hg). However, they are significantly less than those measured with the tensile test reported by Wollensak and Spoerl 25 (5.95 MPa at 8% strain).…”
Section: Discussionsupporting
confidence: 79%
“…20 This suggested that the sclera is stiffer than the cornea, providing key structural support to the eye. The scleral tangent moduli of porcine eyes measured in this study are comparable to the results reported by Pierscoionek et al 26 using the inflation test (0.2-0.5 MPa, the testing IOP ranged from 15-50 mm Hg). However, they are significantly less than those measured with the tensile test reported by Wollensak and Spoerl 25 (5.95 MPa at 8% strain).…”
Section: Discussionsupporting
confidence: 79%
“…The strain upon the applied stress is measured from the lateral elongation, axial apex displacement, 4 shift of mercury droplets attached on the corneal surface, 5,7 or from changes in the corneal radius of curvature. 10,11 A new technique to estimate the corneal biomechanical properties, by measuring the corneal deformation upon air puff applanation, has recently been suggested. 12,13 In all in vitro biomechanical measurements, corneal hydration plays a role as it affects the tissue's mechanical response.…”
Section: Results Flap Curvature Changed With Increased Function Of Imentioning
confidence: 99%
“…The most widespread applied method is strip extensiometry, [1][2][3][4] followed by corneal button inflation, 5,6 and whole globe inflation. [4][5][6][7][8][9][10] In these techniques, a load is applied (typically along one axis in strip extensiometry, or radially by increasing IOP in inflation techniques). The strain upon the applied stress is measured from the lateral elongation, axial apex displacement, 4 shift of mercury droplets attached on the corneal surface, 5,7 or from changes in the corneal radius of curvature.…”
Section: Results Flap Curvature Changed With Increased Function Of Imentioning
confidence: 99%
“…The short-term alteration of IOP did not significantly affect the scleral birefringence in the case of porcine eyes ex vivo. Although it has been known that human and porcine eyes have similar properties of the sclera in some aspects [35][36][37][38], additional studies would be required to show whether the outcome of porcine eyes is interchangeable to human eyes. If it was exchangeable, our result would suggest that the short-term alteration of IOP does not explain the significant negative relationship between the IOP and scleral birefringence of human eyes in vivo.…”
Section: Discussionmentioning
confidence: 99%